Yaupon, Ilex vomitoria - Debbie Miller; Mack Thetford; Chris Verlinde; Gabriel Campbell; Ashlynn Smith (EDIS)
Yaupon is found throughout Florida south to Lake Okeechobee and more broadly throughout the southeast west to Texas and east to North Carolina. The leaves and small twigs of yaupon contain caffeine, and yaupon teas have been consumed by humans for centuries. The fruits and flowers of yaupon attract wildlife, especially birds and pollinators, and it is a larval host plant for Henry’s elfin butterfly (Callophrys henrici) (Lotts and Naberhaus 2017). Yaupon is used in landscaping and can tolerate a wide range of environmental conditions. Several cultivars are available in the horticultural industry. https://edis.ifas.ufl.edu/sg172